PKM Penyuluhan Menjaga Imunitas saat Berpuasa pada Masa Pandemi dan Pemeriksaan Kesehatan Desa Sukorejo Kabupaten Pekalongan - Lestari, Catur Retno; Elawati, Nunung Eni; Wani, Elsayanti; Bulan, Sahari (Manggali, 2021)
Ramadan fasting is a fast that must be done by Muslims during the month of Ramadan for a full month. Diet during Ramadan tends to change, due to differences in meal times compared to other months. The pandemic period coincides with the month of Ramadan which sometimes neglects health and diet during breaking and sahur. It is important to maintain immunity when fasting during a pandemic in order to improve health. This community service activity program is to increase knowledge and understanding of maintaining diet when fasting. The result of this activity was an increase in knowledge about health and continued with medical examinations, namely checking blood pressure, checking blood sugar levels, checking uric acid levels and checking cholesterol levels.